2007
DOI: 10.1103/physrevlett.99.147403
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Radiation from Carbon Nanotubes in the Terahertz Range

Abstract: The thermal radiation from an isolated finite-length carbon nanotube (CNT) is theoretically investigated both in near-and far-field zones. The formation of the discrete spectrum in metallic CNTs in the terahertz range is demonstrated due to the reflection of strongly slowed-down surfaceplasmon modes from CNT ends. The effect does not appear in semiconductor CNTs. The concept of CNT as a thermal nanoantenna is proposed.PACS numbers: 78.67. Ch, 44.40.+a Carbon nanotubes -quasi-one-dimensional carbon molecules… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 28 publications
(46 reference statements)
1
47
0
Order By: Relevance
“…Studies on nanoscale periodic arrays of rectangular-shaped holes revealed band formation of THz nanoresonators [12]. Nemilentsau et al [13] have investigated the application of a finite-length isolated carbon nanotube as a thermal nanoscale antenna in THz range. Batrakev et al [14] and Portnoi et al [15] have given elegant reviews of terahertz processes in carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on nanoscale periodic arrays of rectangular-shaped holes revealed band formation of THz nanoresonators [12]. Nemilentsau et al [13] have investigated the application of a finite-length isolated carbon nanotube as a thermal nanoscale antenna in THz range. Batrakev et al [14] and Portnoi et al [15] have given elegant reviews of terahertz processes in carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 SWCNTs with different chiralities exhibit either semiconducting or metallic properties, providing great flexibility for a variety of THz and plasmonic applications, including sources, [5][6][7] detectors, 3,5 antennas, 8,9 and polarizers.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of proposals exist for using carbon nanotubes for THz emitters and detectors [48,49,53,54,56,115]. Kibis et al [115] demonstrated that quasi-metallic carbon nanotubes emit THz radiation when a potential difference is applied across their ends.…”
Section: Thz Emitters and Detectorsmentioning
confidence: 99%